Pemanfaatan Sampah Sayur Dari Pasar Tradisional Untuk Produksi Bioetanol - Novirina Hendrasarie; Dimas Eka Mahendra (Fakultas Teknik, 2020)
Vegetables that do not sell and rotten will be thrown away. This makes the volume of waste increases every day. Vegetable waste that is no longer being sold, could reprocessed into useful products and selling value. The purpose of this research is to use vegetable waste to become bioethanol raw material, which have economic value. The selected vegetable waste was from potatoes, carrots, cabbage, cassava, chicory, and green mustard, because they have higher carbohydrate content than other vegetable waste. The bioethanol product produced will be measured by its bioethanol content and fermentation time. These two factors, affect the quality of the bioethanol produced. The microorganism used in this study was Saccharomyces cerevisiae. These microorganisms are in bread yeast and tape yeast, which are also examined for their effectiveness in the production of this vegetable waste bioethanol. From this study, producing bioethanol with the highest ethanol content of 15% v / v, produced in the interaction of bread yeast and 6 days’ fermentation time. Meanwhile, from the production using yeast tape, obtained ethanol levels of 13% v / v. Bioethanol from vegetable waste is not only to reduce the burden of waste generation, but can be used as an alternative energy to replace fuel.